The Impact of Service Recovery Strategies on Customer Satisfaction "A Field Study on Customers of The Tourist Restaurants in Hama City" (Journal of Hama University, 2021)
This research aimed to study the impact of service recovery strategies on customer satisfaction in a new environment within the Syrian community, which is tourist restaurants in Hama city, and to achieve the objectives of the study and test its hypotheses, the researcher collected the necessary data by designing a questionnaire that was distributed to the individuals of the sample. Which were chosen randomly from the study population, where (389) questionnaires valid for statistical analysis were retrieved, and by using the SPSS V.26 program for statistical analysis, the study found a number of the most important results are that, there is a positive significant effect of the dimensions of service recovery strategies on customer satisfaction separately, and is considered the most apology strategy influential by 30.9%, while considered at least influential by 18.1% amounted to the response speed strategy. The study recommended several recommendations, the most important of which are, strengthen the culture of apology, compensate customers who are exposed to a situation of service failure and solve their problems with the required speed in order to increase their level of satisfaction.